Analisis Hubungan Pola Asuh Anak Dengan Stunting Pada Balita - Ishak, Syamsopyan; Rate, Suherman; Dewanti, Ritma; Dahro, Ahmad (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2024)
Background: Stunting describes a chronic malnutrition status during growth and development since early life. Toddlerhood is a period that is very sensitive to the environment so that more attention is needed, especially nutritional adequacy. Methods: ; The type of research used is quantitative descriptive with a Cross Sectional Study approach. The sample in this study was some toddlers with a purposive sampling technique of 94 toddlers. Results: The results of the study showed that knowledge with a p value (0.008), attitude p (0.004) and action p (0.001) were variables related to stunting in toddlers and the results of the statistical analysis of the logistic regression test on three variables, knowledge was the most dominant variable with stunting in toddlers with an Exp value (B) = 0.248. Conclusion: Knowledge of parenting patterns is the most dominant variable with stunting in toddlers.